THE PROMOTING ROLE OF FREE ECONOMIC ZONES IN UZBEKISTAN’S IMPORT AND EXPORT TRADE: FROM THE PERSPECTIVE OF INDUSTRIAL AGGLOMERATION AND POLICY EMPOWERMENT (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Free Economic Zones (FEZs) are the core carriers for upgrading Uzbekistan’s import and export trade. From the perspective of industrial agglomeration and policy empowerment, this paper adopts case study and other methods to explore their operational mechanisms and practical status. The research shows that through policy incentives, industrial agglomeration, and factor concentration, FEZs have promoted the expansion of foreign trade scale and structural optimization—FEZs accounted for 29% of the country’s total foreign trade in 2025, with the proportion of high-value-added product exports reaching 48%. However, problems such as low-quality industrial agglomeration, policy implementation deviations, inadequate infrastructure, talent shortages, and weak risk prevention persist. Corresponding suggestions including optimizing layout and strengthening policy execution are proposed.
Keywords: Uzbekistan; Free Economic Zone (FEZ); import and export trade; industrial agglomeration; policy empowerment